2016
DOI: 10.1093/pcp/pcw029
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Evolution and Functional Divergence of MYB Transcription Factors in Chinese White Pear (Pyrus bretschneideri)

Abstract: The MYB superfamily is large and functionally diverse in plants. To date, MYB family genes have not yet been identified in Chinese white pear (Pyrus bretschneideri), and their functions remain unclear. In this study, we identified 231 genes as candidate MYB genes and divided them into four subfamilies. The R2R3-MYB (PbrMYB) family shared an R2R3 domain with 104 amino acid residues, including five conserved tryptophan residues. The Pbr MYB family was divided into 37 functional subgroups including 33 subgroups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 140 publications
15
74
0
Order By: Relevance
“…The number of OfMYBs in some subgroups (Of1, Of6, Of9, Of10, Of23, Of26, Of31, Of33) was far greater than that of AtMYBs, which suggested that MYBs were subjected to duplications after the divergence of sweet osmanthus and Arabidopsis. This has been observed in pear and soybean [6,7]. The subgroup Of17 did not contain any AtMYB members, which indicated that these MYB family members in sweet osmanthus may have specialized roles.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The number of OfMYBs in some subgroups (Of1, Of6, Of9, Of10, Of23, Of26, Of31, Of33) was far greater than that of AtMYBs, which suggested that MYBs were subjected to duplications after the divergence of sweet osmanthus and Arabidopsis. This has been observed in pear and soybean [6,7]. The subgroup Of17 did not contain any AtMYB members, which indicated that these MYB family members in sweet osmanthus may have specialized roles.…”
Section: Discussionmentioning
confidence: 62%
“…As increasing numbers of plants have undergone genome sequencing, many 2R-MYB TFs have been characterized. For example, 126 members of the 2R-MYB gene family were reported in Arabidopsis thaliana [3], 244 in soybean [6], 185 in pear [7], 122 in tomato [8], and 114 in moso bamboo [9]. A conserved N-terminus and variable domain in the C-terminus ensure that MYB genes play comprehensive regulatory roles in plant growth and development [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…By reason of Arabidopsis was a model species in plants, and all the gene of MYB had almostly studied. In particular, all 27 evolutionary branches of R2R3-AtMYBs had annotations [22,36]. Therefore, in order to predict the function of the HrMYBs, a co-constructed ML phylogenetic tree by R2R3-MYB proteins of Arabidopsis and Hippophae rhamnoides were utilized in our study (Fig.…”
Section: Putative Functions Of the Sea Buckthorn R2r3-myb Genementioning
confidence: 99%
“…Duplication events have been widely studied in Rosaceae species by the analysis of various gene families including F-box genes (Wang et al 2013), heat shock factors (Qiao et al 2015), MYB and WRKY transcription factors (Huang et al 2015;Li et al 2016), lipoxygenases (Li et al 2014), sugar transporters (Li et al 2015), and cation proton antiporters (Zhou et al 2016). In this study, based on the chromosome location of each PDI gene, the synteny of chromosome segments containing PDI gene(s) was analyzed among three different phenotypical species: drupe (peach), pome apple, and berry (strawberry).…”
Section: Phylogeny and Duplication Events Of Pdi Genes In Fruit Treesmentioning
confidence: 99%